2016
DOI: 10.1002/rnj.253
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Levels: Applied to Select Fall and Fall Injury Prevention Practices

Abstract: Problem: Rehabilitation nurses know the impact of injury on function, independence, and quality of life, complicated by age-related changes associated with decreased strength, endurance, reserve, frailty, and social and financial resources. Multidisciplinary teams are essential to provide expert, age specific health care delivery to this vulnerable population across settings of care. Purpose: The purpose of this article is to apply level of evidence rating scales to identify the best practice interventions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…Our results indicated that fall prevention/management policies and procedures in SCI rehabilitation were similar to those implemented in acute care settings [22]. Fall prevention/management policies and procedures from the organizations sampled were formed at an organizationallevel, as there was limited evidence for unit-level or population-specific fall prevention/management strategies [3,23]. However, it has been suggested that the current fall prevention evidence fails to support the specialty needs of rehabilitation, and specifically SCI rehabilitation [12,23].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Our results indicated that fall prevention/management policies and procedures in SCI rehabilitation were similar to those implemented in acute care settings [22]. Fall prevention/management policies and procedures from the organizations sampled were formed at an organizationallevel, as there was limited evidence for unit-level or population-specific fall prevention/management strategies [3,23]. However, it has been suggested that the current fall prevention evidence fails to support the specialty needs of rehabilitation, and specifically SCI rehabilitation [12,23].…”
Section: Discussionmentioning
confidence: 87%
“…The lack of direction for assessing the risk of falls in rehabilitation settings [23] is demonstrated in our analysis. For instance, all sites used different risk assessments.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations